Increased systemic blood pressure and arterial stiffness in young adults born prematurely. (22nd August 2014) - Tauzin, L.; Rossi, P.; Grosse, C.; Boussuges, A.; Frances, Y.; Tsimaratos, M.; Simeoni, U.
<x content-type="archive" xml:space="preserve">Abstract</x> Recent studies have shown that a low birth weight is a risk factor for increased systemic blood pressure (BP) in adulthood. Further, systemic BP and arterial stiffness (AS) are reported to be increased in adolescents born prematurely. The purpose of this study was to characterize systemic BP and AS in young adults born preterm. Systemic BP was measured using an automated oscillometric device. AS was assessed by measuring the right carotid–radial pulse wave velocity (PWV) using a validated non-invasive automated method. Systemic BP, pulse pressure, and PWV [mean (confidence intervals)] were compared between 16 adults (age 21 years) born preterm (age at birth 32 weeks of gestation) with a birth weight (1710 g) appropriate for their gestational age and 15 adults (21 years) born at term (40 weeks of gestation) with a birth weight (3430 g) appropriate for their gestational age. Adults born preterm had a significantly higher systolic BP [122 mmHg (114–144) v. 112 (106–127)], mean BP [89 mmHg (86–98) v. 84 (81–91)], diastolic BP [69 mmHg (66–76) v. 65 (62–78)], pulse pressure [54 mmHg (47–72) v. 47 (42–60)], and PWV [7 m/s (6.3–8.6) v. 6.4 (5.8–8)] than did those born at term. Our findings suggest that young adults with a low birth weight due to preterm birth have increased systemic BP and AS. Accordingly, preterm birth may predispose individuals to cardiovascular diseases in adulthood due to increased AS.